PENGEMBANGAN E-MODUL BIOLOGI APLIKATIF-INTEGRATIF BERBASIS PEMBELAJARAN BERDIFERENSIASI UNTUK MATERI VIRUS DI SMA - Asmayani; Seprida, Riski; Rosmiati, Etti (Jurnal Biogenerasi, 2025)
This study aims to develop an applicative-integrative E-Module (Electronic Module) based on differentiated learning as a form of support for the implementation of the Independent Curriculum in Senior High Schools. This study uses a Research and Development (R&D) approach by adapting the 4D development model developed by Thiagarajan, Semmel, and Semmel. This model consists of four main stages, namely Define, Design, Develop, and Disseminate. Thus, it can be concluded that the RPP for the Virus material is included in the "valid" category and is ready to be implemented. Based on the practicality criteria that have been set, it can be concluded that the Biology E-Module for Virus Material from the aspect of teacher response is called "Practical". The percentage of students with a minimum level of competency mastery in the competent category is 92%. So according to the success criteria, namely a minimum of 90% of students in the minimally competent category, the mastery of student competencies has met the classical standards.